The factors influencing investment decision among youth in ASNB Putrajaya / Aqiilah Nawwar Mohamad - Mohamad, Aqiilah Nawwar (2017)
This study is focus on individual investment and specific to the unit trust. The objective of this study is to study the factors influencing investment decision among youth in Amanah Saham Nasional Berhad at Putrajaya. It is specific to the youth because nowadays, youth are less interested in making the investment and they do not interest to plan their financial. But for the country they need the young generation to develop the economy in future. Therefore, next generation are very important to the economy growth. This issue has proved by Bursa Malaysia in which they revealed that the younger Malaysian generation is not active in the investment (Ganesan, 2012). Therefore this study has developed to see the factors influencing investment decision among youth. The definition of youth has been defined by the National Youth Development Policy of Malaysia as people aged between 15 to 40 years old. Therefore, for this study the focus is youth between ages 15 to 40 years old that has invest in ASNB Putrajaya. While the focus for this study is on several factors that influence the investment decision in previous research. The factors such as self image/firm image coincidence, accounting information, advocate recommendation, personal financial needs, and neutral information. These factors are independent variable in this study while the dependent variable is investment decision. The aim of this study is to see either this independent variable has a relationship with investment decision among youth in ASNB Putrajaya. The area of study is at Putrajaya and be focus on the investment at ASNB. 100 questionnaires are distributed to the respondent and be analyse using quantitative method approach. The primary data collection is survey questionnaire and secondary sources such as journal and internet.